Learning Society and Sustainable Development: adult education re-search that expands the territories - Soonghee Han (Firenze University Press, 2019)
The field of adult education research has been and will continue to expand. In this process, one of the notable changes is that the units of research extend from individuals to collectives. Educational researches has traditionally studied an individual's learning and change as a unit of research. However, social change is difficult to account for in individual units, and most of the major changes, especially those involving social changes have been made through collective learning and changes beyond the individual level. The research fields that have grown in the area of adult education, such as organizational learning, community learning, expansive learning or team learning, started from this interest.